An axiomatic approach to the analysis of pace of production - Завадскас, Э.К.; Подвезько, В.; Андрушкявичюс, А. (Proceedings of National Aviation University (archive), 2004)
To analyse the performance of production systems, a relevant parameter representing the steady pace of manufacturing processes may be considered its quantitative measure. When applied to initial data, various indices of the steady pace often yield different and even conflicting results. The application of logically consistent axioms to a set of indices allows us to identify those of them which actually describe a steady pace of production.